King Coo - Stower, Adam (David Fickling Books, 2018)
"Ben Pole is on the run from his arch-enemy Monty Grabbe when he discovers a forest with rope swings, water slides, Herbert the Wombat and best of all King Coo. Cow-pat-a-pults and Slug Pulp to the ready! Monty and his gang have a dastardly plan, and Ben and Coo need to come up with their best invention yet..."--Back cover
Originally published: 2017
Keywords: Bullies / Juvenile fiction; Schoolboys / Juvenile fiction; Humorous stories; Fantasy fiction; Mobbing; Schulkind; Kinderbuch